Reliability of estimating active drag in swimming using the assisted towing method with fluctuating speed - Hazrati, P.; Sinclair, P. J.; Ferdinands, R. E.; Mason, B. R. (Sports Biomechanics, 2016)
The reliability of active drag values was examined using a method that compared free swim speed with measurements taken by towing swimmers slightly faster than their maximum swim speed, while allowing their intra-stroke speed fluctuations. Twelve national age and open level swimmers were tested on two alternate days (Day 1 and Day 2). All participants completed four maximum swim speed, three passive drag and five active drag trials on each of the days. The reliability was determined using within-participant intra-class correlation coefficients (ICC) within each day and between the days. The ICCs for Day 1 and Day 2 were 0.82 and 0.85, respectively, while the comparison of the mean active drag values between days was 0.93. The data showed that the assisted towing method (ATM) with fluctuating speed was only moderately reliable within a single test. However, this method was more reliable when using the average value of active drag from both days (ICC=0.93). This study identified that the ATM method with fluctuating speed had moderate reliability within-participant trials on values in a single day but high reliability for the average active drag values across different days.